2020
DOI: 10.1029/2019wr025943
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Factors Driving Flood Losses in Households Affected by Different Flood Types

Abstract: Flood loss data collection and modeling are not standardized, and previous work has indicated that losses from different flood types (e.g., riverine and groundwater) may follow different driving forces. However, different flood types may occur within a single flood event, which is known as a compound flood event. Therefore, we aimed to identify statistical similarities between loss-driving factors across flood types and test whether the corresponding losses should be modeled separately. In this study, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…This supports the hypothesis that the overall (hydraulic) severity of a flood pathway is more important for the perceived psychological burden than the general flood type (see Laudan et al, 2020). The results further support studies that suggest developing pathway-specific loss models (Vogel et al, 2018;Mohor et al, 2020). 350 At this point, the question arises whether and to which degree flood pathways also govern coping options.…”
Section: Financial Flood Impacts and Perceived Recovery 310supporting
confidence: 81%
“…This supports the hypothesis that the overall (hydraulic) severity of a flood pathway is more important for the perceived psychological burden than the general flood type (see Laudan et al, 2020). The results further support studies that suggest developing pathway-specific loss models (Vogel et al, 2018;Mohor et al, 2020). 350 At this point, the question arises whether and to which degree flood pathways also govern coping options.…”
Section: Financial Flood Impacts and Perceived Recovery 310supporting
confidence: 81%
“…Yet loss estimation remains challenging, even for direct losses that can be more easily determined than indirect losses (Figueiredo et al, 2018;Vogel et al, 2018;Amadio et al, 2019;Meyer et al, 2013). Numerous methods of inferring flood damage from field or survey data have been tested, if not validated, with varying degrees of success (Gerl et al, 2016;Molinari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…floods from levee breaches, riverine floods, surface water floods, or rising groundwater floods). Mohor et al (2020) used this database to explore the most relevant factors for estimating relative loss of residential buildings with a regression model. From a larger pool of candidate variables, the authors selected 13 predictors of the flood hazard, building characteristics, and preparedness, including flood type as an indicator, and suggested that the influencing factors contribute with different magnitudes across flood types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Austrian Federal Railways (ÖBB) holds an objectspecific flood damage database for railway infrastructure and operation in Austria (Moran et al, 2010;Kellermann et al, 2016). This database incorporates information about the affected infrastructure object and resulting service disruptions, the structural damage and corresponding repair costs, the hazard characteristics, and possible mitigation measures.…”
Section: Natural Hazard Damage Data On the Object Scalementioning
confidence: 99%